2020
DOI: 10.1159/000510925
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Refractive Status and Ocular Biometric Parameters in Primary Angle Closure Disease

Abstract: Introduction: The aim of the study was to evaluate the refractive status and ocular biometric parameters in subjects with angle closure in Malaysia. Methods: This cross-sectional study was conducted on 171 primary angle closure patients (268 eyes). Visual acuity, refraction, and ocular biometry (central anterior chamber depth [ACD], axial length [AL], and lens thickness) were recorded. Vitreous cavity length (VL) and relative lens position (RLP) were calculated. Results: A total of 92 Primary Angle Closure Sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
2
9
2
Order By: Relevance
“…However, recent studies propose that lens parameters would be stronger determinants of anterior chamber depth than axial length and that an increased thickness and anteriorly positioned lens, as occurs in hyperopic eyes, would confer a greater risk of PAC-DS in these subjects. 37 In people with diabetes and higher values of blood glucose, refractive changes have been reported with controversial findings. 38 Most studies suggest that a higher risk of myopia could increase in hyperglycemic subjects, which could explain by changes in the structure and biochemical composition of the lens.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies propose that lens parameters would be stronger determinants of anterior chamber depth than axial length and that an increased thickness and anteriorly positioned lens, as occurs in hyperopic eyes, would confer a greater risk of PAC-DS in these subjects. 37 In people with diabetes and higher values of blood glucose, refractive changes have been reported with controversial findings. 38 Most studies suggest that a higher risk of myopia could increase in hyperglycemic subjects, which could explain by changes in the structure and biochemical composition of the lens.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were in concordance with a previous study, which reported that persons with myopia with angle closure had longer axial length and vitreous length, but similar ACD to those without myopia but with angle closure. 17 Loh et al 27 found that relative lens position is more forward in patients with myopic angle closure. In addition, we observed an age-related tendency toward shallower anterior chambers and thicker lenses in persons with myopia with PACD, consistent with a prior prospective observational study conducted in healthy subjects.…”
Section: Discussionmentioning
confidence: 97%
“…ACD and ACW are key factors in the diagnosis of glaucoma. ( Chen et al, 2013 ; Loh et al, 2021 ) For instance, shallow ACD may increase the risk of angle-closure glaucoma. In addition, ACD is a critical parameter in the implantation of pIOL.…”
Section: Discussionmentioning
confidence: 99%